A Randomized Comparative Evaluation Of Effects Of Dexmedetomidine As An Adjuvant With Bupivacainein Supraclavicular Block In Crf Patients Undergoing Basilic Vein Transposition Surgery - Nazneen Kalim, Adnan Ali Baloch, Nida Shafqat, Vijay Kumar, Zamir Ahmad, Altaf Hassan, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare analysis of bupivacaine in supraclavicular block with dexmedetomidine bupivacaine in supraclavicular block in chronic renal failure patients undergoing basilica vein transposition surgery. Methodology: Double-blind randomised control trial. Department of Anaesthesia, Sindh Institute of Urology and Transplantation, Karachi, from September 1st, 2021, to February 28th, 2022 Seventy chronic renal failure patients undergoing elective basilic vein transposition surgery were enrolled. Patients were divided into two groups, in which 35 patients in group A received bupivacaine (0.25%) in 28mL plus dexmedetomidine (1ug/kg) diluted to 2 mL, and 35 patients in group B were injected with bupivacaine (0.25%) in 28 mL plus 2mL of normal saline. Results: The mean time of onset of sensory blockade was comparatively higher in group B as compared to group A. Similarly, the onset of motor block time was also higher in group B as compared to group A, and the duration of motor block did not show any significant results between groups, and the duration of motor block was not statistically significant between groups [p = 0.404]. Conclusion: The combination of bupivacaine and dexmedetomidine appeared to be useful for onset time and prolongs the duration of analgesia in supraclavicular brachial plexus block. Keywords: Chronic kidney disease, Dexmedetomidine, Supraclavicular brachial plexus block